The making of polities : Europe, 1300-1500 - Watts, John (John Lovett), 1964- (Cambridge medieval textbooks., 2009)
"This major survey of political life in late medieval Europe - the first for more than thirty years - provides an entirely new framework for understanding the developments that shaped this turbulent period. Rather than emphasising crisis, decline, disorder or the birth of the modern state, this account centres on the mixed results of political and governmental growth across the continent. The age of the Hundred Years War, schism and revolt was also a time of rapid growth in jurisdiction, taxation and representation, of spreading literacy and evolving political technique. This mixture of state formation and political convulsion lay at the heart of the 'making of polities'. Offering a full introduction to political events and processes from the fourteenth century to the sixteenth, this book combines a broad, comparative account with discussion of individual regions and states, including eastern and northern Europe alongside the more familiar west and south."--Publisher description